The Impact of Chitosan-Divergicin Film on Growth of Listeria monocytogenes in Cold-Smoked Salmon - Benabbou, Rajaa; Subirade, Muriel; Desbiens, Michel; Fliss, Ismail (Frontiers in Microbiology, 2018)
The aim of this study was to evaluate the impact of chitosan film, with bacteriocin divergicin 35 incorporate, on growth of Listeria monocytogenes in Cold smoked salmon. The simples of Cold-smoked wild salmon were inoculated with Listeria monocytogenes and treated with chitosan (100 kDa, 94.7% de-acetylated) and divergicin M35 was stored for three weeks at 4–8°C. The compounds were applied to the fish flesh in the form of solution or dried film. The film reduced L. monocytogenes to below the detection limit (<50 cfu/g) and kept total counts below 104 cfu per g compared to 109 cfu per g in control samples while the effectiveness of the solution was very limited. The inhibitory activity of the film lasted for three weeks, while the solution had no effect on L. monocytogenes counts measured on day 14. The film provided a better preservation of fish color (redness) and firmness than others treatments, while the solution had little impact on these parameters. It kept the volatile basic nitrogen (17.5 mg N/100 g) below the control value 29.9 mg N/100 g. Divergicin-loaded chitosan film thus may represent an interesting alternative for the bio-preservation of cold-smoked fish.